Alexithymia and Impaired Interoceptive Awareness in Patients with Anorexia Nervosa - Doshchuk Марія; Dzeruzhynska Наталія (Psychosomatic Medicine and General Practice, 2026)
Background. Anorexia nervosa (AN) remains one of the most severe clinical challenges in modern psychology and psychiatry. In recent decades, there has been a steady upward trend in the prevalence of this disorder, especially among adolescents and young adults. The disease is characterized not only by the highest mortality rate among all psychiatric disorders but also leads to profound social maladaptation: the destruction of interpersonal ties, impaired professional fulfillment, and a severe deterioration in the quality of life. Traditional therapies often focus on behavioral manifestations, ignoring the fundamental mechanisms of emotional and bodily dysregulation, which leads to a high risk of relapse. Objective. To improve the diagnosis and psychological interventions for individuals with AN through theoretical justification and empirical investigation of the role of alexithymia and interoceptive impairments in the pathogenesis of this disorder. Materials and Methods. A total of 84 individuals were examined (30 in the clinical group with AN symptoms, 54 in the control group). The psychodiagnostic battery included: TAS-20, MAIA-2, EAT-26, SCOFF, HADS, and CQLS. Statistical processing was performed using the Mann-Whitney U test, Spearman’s and Pirson’s correlation analysis. Results and Discussion. A clinically significant level of alexithymia was found in the clinical group (68.42±9.80). The phenomenon of an «interoceptive disconnect» was established: with a preserved ability to notice bodily signals, patients demonstrate critically low body trust (1.1). Alexithymia acts as a mediator linking anxiety with pathological eating attitudes (r=0.54) and a decreased quality of life (r=−0.68). Conclusions. The necessity of shifting the therapeutic focus from weight control to the restoration of interoceptive trust and emotional mentalization has been demonstrated. Keywords: anorexia nervosa (AN), alexithymia, interoception, quality of life, eating behavior.